Synthesis of benzotetraazaadamantanes and their derivatives - A. H. Shukkur; A. I. Kuznetsov (Тонкие химические технологии)
The condensation of three-components formaldehyde and mixture of ammonia and o-phenylenediamine gave novel 4-bеnzо-1,3,6,8-tetraazatricyclo[3.3.113,8]-4- undecane 5 а which was identified it’s structure by x-ray crystallographic and 1 Н NMR and MS spectroscopy methods